Political Leadership Malay Party - Fadzli, Adam; Hailan, Salamun; Mustakimah, Husin; Firdaus Khairi, Abdul Kadir (2018)
Islamic political leadership that tends to practices transparently can evoke a sense of responsibility among the people to uphold the tenets of Islam through state and governance system. The public support are seen unattractive when leadership practice among the leader is weak, corrupted and do not have a strong commitment to the interests of the nation and religion. This study aimed to explore the practice of political parties between PAS and Ulv1140 leadership are in line with Islam and to review the practice of building a knowledgeable culture, empowerment and management of community development This qualitative study used the methods of interviews and observations as well as other relevant documents to obtain data focusing on the state of Kelantan and Terengganu. Rabbani's leadership model will be used to see how far the appreciation of the current political leadership practices among the current local leaders with the practice of leadership in Islam.